Studies on thermoluminescence parameters of erbium doped Y2O3 nanophosphors - Bhuie, Manmeet kaur; Bisen, D P; Bramhe, Nameeta (Recent Research in Science and Technology, 2012)
The thermoluminescence (TL) glow curve of Y2O3:Er3+ with different radiation time has been studied. The experimental glow curve shows the presence of two peaks at linear heating rate 10°C/min. The activation Energy and frequency factor are determined by thermoluminescence glow curve.